Late Gastrointestinal Tolerance After Prostate Radiotherapy: Is the Anal Canal the Culprit? A Narrative Critical Review - Sargos, Paul; Faye, Mame Daro; Bacci, Manon; Supiot, Stéphane; Latorzeff, Igor; Azria, David; Niazi, Tamim M.; Vuong, Te; Vendrely, Véronique; de Crevoisier, Renaud (Frontiers in Oncology, 2021)
Introduction: Late gastro-intestinal toxicities (GIT) secondary to pelvic radiotherapy (RT) are well described in the literature. Late GIT are mainly related to rectal or ano-rectal irradiation, however involvement of the anal canal (AC) in the occurrence of late GIT remains poorly de-scribed and understood. Material and method: The aim of this work was to establish a potential role of the AC in the development of late GIT after prostate irradiation and identify predictive factors that could be optimized in order to limit these toxicities. We identified original articles published between June 1997 and July 2019, relating to late GIT after RT for localized prostate cancer and for which AC was identified independently. Articles defining the AC as part of an anorectal or rectal volume only were excluded. Results: A history of abdominal surgery or cardio-vascular risk, anticoagulant or tobacco use and the occurrence of acute GIT during RT increases the risk of late GIT. A dose-effect relationship was identified between dose to the AC and development of late GIT. Identification and con-touring of the AC and adjacent anatomical structures (muscles or nerves) is justified to apply specific dose constraints. As a limitation, our review treated mainly on 3DCRT which is no longer the standard of care nowadays; we did not identify any reports in the literature treating of moderately hypofractionated RT for the prostate and AC specific dosimetry. Conclusion: These results suggest that the AC may have an important role in the development of late GIT after pelvic RT for prostate cancer. The individualisation of the AC during planning should be recommended in prospective studies.